Can We Create an Arteriovenous Fistula for Hemodialysis through 0.5–1.0 cm Incision without Using Vascular Clamps? - Kalpesh J. Gajiwala (Indian Journal of Plastic Surgery)
Background A native arteriovenous fistula (AVF) is a gold standard for renal replacement therapy, where regular hemodialysis is the mainstay of survival in the majority of patients suffering from end-stage renal disease. Appropriate vascular clamps are routinely used to occlude an artery and a vein before an arteriotomy or a venotomy is done to prevent blood loss and have a clear field and an ease of anastomosis. The title makes one wonder, is it then possible to create an AVF without using vascular clamps? And through incisions as small as 0.5to 1.0 cm? This is made possible by a very simple new technique, presented here, that helps to occlude vessels to create an AVF through minimal access, and minimize blood loss and postoperative pain. Material and Method Total 622 AVFs were created between 1998 and 2019. With regular forceps or an AVF platform (design given), an AVF was created without using a vascular clamp. Total 321 cases were operated with 0.5 to 1.0 cm and 215 cases within 1.5 cm skin incision approach. Results There were ~85% successful functional fistulas. The blood loss was negligible, and only one in three required pain killer in postoperative period. Conclusion A simple new technique described here makes it possible to create a functional AVF through a small incision, without using vascular clamps.